RETRACTED: Analysis of climate risks impact on railway infrastructure and adaptation measures system development - Akhtyamov R.G.; Chirkov N.S. (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001